Trends in COVID-19 patient characteristics and mortality throughout the pandemic: insights from a portuguese single-centre study - Von Rekowski, Cristiana (2024)
As SARS-CoV-2 continues to circulate globally and new variants emerge, it remains relevant to gather data on the affected patients’ clinical characteristics and outcomes to understand how individual factors and public health measures affect prognosis. Thus, we analyzed data of 870 ICU patients admitted for COVID-19 across two distinct phases of the pandemic: before and after the introduction of immunization. Experimental results showed that vaccination significantly impacted patient demographics after the third wave, and that waves number two and three, dominated by the EU1 and Alpha variants, had higher mortality. Older age, the need for invasive mechanical ventilation, and hematologic cancer were significantly associated with an increased risk of death in the adjusted multivariable model (AUC: 0.778, 95% CI 0.746-0.810, p<0.001). As the pandemic progressed, while some public health interventions influenced the observed trends, individual patient characteristics had a more substantial impact on their outcome.